3D numerical simulations of passive mixing in a microchannel with nozzle-diffuser-like obstacles - Ritter, Paul; Osorio Nesme, Anuhar; Delgado, Antonio (International Journal of Heat and Mass Transfer, 2016)
A novel passive chaotic advection micromixer with periodic nozzle-diffuser-like (NDL) obstacles is proposed. Lattice Boltzmann simulations of two incoming flows were performed for Reynolds numbers in the range 1 łeq Re łeq 100 and two Schmidt numbers Sc = 1 and 50. The numerical study focuses on the evaluation of the mixing efficiency of the new design and the analysis of mass transfer as a function of the Péclet number. The flow was identified as spatially periodic. The results are compared with those for a plain rectangular channel. The asymmetric design and placement of the obstacles lead to splitting and recombination of the flows, promoting transverse flow. Two principal characteristics of chaotic advection were observed at high Pe: helical, intertwined streamlines and hyperbolic points in transverse planes. The mixing efficiency was found to increase with channel length, whereas for the proposed channel the mixing efficiency was observed higher than that for the rectangular channel for Pe > 100.
UnivIS-Import:2018-09-11:Pub.2016.tech.ITC.stmmec.3dnume
Keywords: Chaotic advection; Microchannel; Mixing

Detection of foreign bodies in closed food containers supported with fluid-solid-interaction analysis - schmidt, Tobias R. H.; Osorio Nesme, Anuhar; Forstner, Judith; Beronov, Kamen; Benning, Rainer; Delgado, Antonio (American Society of Mechanical Engineers, Pressure Vessels and Piping Division (Publication) PVP, 2010)
UnivIS-Import:2017-12-18:Pub.2010.tech.ITC.stmmec.detect

Flow characterization in periodic microchannels containing asymmetric grooves - Osorio Nesme, Anuhar; Delgado, Antonio (Fluid Dynamics Research, 2017)
Characterization of two-dimensional flows in microchannels with anisotropic periodic grooves is numerically carried out by using the lattice Boltzmann method. Periodically placed microstructures, consisting of novel nozzle-diffuser-like grooves are deliberately designed to introduce a flow-direction dependent resistance. Simulations were conducted for a low-to-moderate Reynolds number in the laminar-transition flow regime. Different channel geometries, defined by the half-angle of the periodic grooves are considered. The influence of the half-angle on both the flow field and the onset of oscillatory flow regime at different driving body forces is analyzed. At a low Reynolds number, the flow is observed stationary and fully reversible, regardless of the groove geometry. In this regime, higher Reynolds numbers were observed when the geometry acts as a diffuser (negative flow) than as a nozzle (positive flow) for a given driving body force. At sufficiently high Reynolds number the flow turns from a steady state to a time-dependent oscillatory regime through a Hopf bifurcation. Successive flow bifurcations lead the flow structure from a periodic regime to a quasi-chaotic regime with three-dimensional structures. The onset of unsteady flow occurs earlier for positive flows and geometries with small half-angles. For higher driving forces, there is a reduction in the volume flow rate due to the advected material in the transversal direction, causing consequently a decrease in the Reynolds numbe
UnivIS-Import:2018-02-22:Pub.2017.tech.ITC.stmmec.flowch
Keywords: fluid mechanics; grooved channel; lattice Boltzmann method; unsteady flow

Flow rectification and reversal mass flow in printed periodical microstructures - Osorio Nesme, Anuhar; Rauh, Cornelia; Delgado, Antonio (Engineering Applications of Computational Fluid Mechanics, 2012)
The present paper aims at the study of flow rectification, reversal mass transport and flow characterization occurring in two-dimensional channels with designed asymmetric microstructures periodically placed in the streamwise direction using the lattice Boltzmann method. The present contribution deals with microchannels containing nozzle-diffuser-like structures (grooves), which promote net flow in a preferential direction for flows with time-dependent alternating direction. Different geometries are analyzed by varying the halfangle φ which defines the groove. The influence of φ on the flow rate ratio Q net and on flow rectification efficiency ε is presented for low-to-moderate-Reynolds-number flows. It is shown that geometries with large angles exhibit poor flow rectification during the steady state regime. In general, for all geometries studied, the flow rectification occurs in the diffuser direction for subcritical flows (stationary flows) and in the nozzle direction for supercritical flows (self-sustained oscillatory flows). Grooves with φ =11.31° and φ. 26. 56° perform with the highest rectification efficiency but only at high driving body forces.
UnivIS-Import:2015-03-09:Pub.2012.tech.ITC.stmmec.flowre
Keywords: Flow rectification; Lattice Boltzmann method; Rectification efficiency; Reversal mass transport

Food foams simulations by the means of multicomponent lattice Boltzmann Method - Mobarak, Mohammad Mobarak; Gatternig, Bernhard; Osorio Nesme, Anuhar; Hussein, Mohamed; Delgado, Antonio (9th European Postgraduate Fluid Dynamics Conference, 2019)

Heat transfer in deformable foams by the means of multicomponent Lattice Boltzmann Method - Mobarak, Mohammad Mobarak; Gatternig, Bernhard; Hussein, Mohamed; Osorio Nesme, Anuhar; Delgado, Antonio (Proceedings der 27. GALA-Fachtagung "Experimentelle Strömungsmechanik", 2019)
Foam propagation is a complex and challenging topic in food and chemical industry. Foam exists in several industrial applications such as food supply and discharge pipes, dairy products tanks and rectification columns. Foams often influence the mass, momentum and energy transport as well as the biochemical reactions. Consequently, this leads to a significant additional consumption of time and energy, and also to a loss of product quality and safety. The proposed approach is to apply a multi-component Lattice Boltzmann method, namely Shan-Chen pseudopotential model coupled with thermal LBM in order to simulate the complex heat transfer process in foams, taking into account the foam dynamics and deformation. The approach is to use multi-distribution functions for the multicomponent flow and temperature fields considering the different physical parameters for each phenomenon. The Lattice Boltzmann Method (LBM) has recently gained great attention in thermal flow field modelling, especially in complex media. One great advantage of the method is that it handles complex geometries and obstacles in a simple manner. LBM also gained much attention and success in the field of multicomponent and multiphase flows, one benefit is that it does not need an explicit additional algorithm for interface tracking. These simulations will provide a deeper insight in the foam dynamics and heat transfer process inside this nonhomogeneous medium. This can provide the basis for a prediction tool that regards the foaming causes and effects in several industrial processes. Several Industrial sectors with various products like beverages and milk can benefit from this tool, as the foaming in beverages’ filling and dairy production can be controlled and optimized on this basis. Other applications are chemical production facilities that deal with columns and evaporators which also encounter critical foaming issue
Keywords: Lattice Boltzmann Method; Multiphase-Multicomponent flow; Shan-Chen Pseudopotential Model; Thermal Flows; Food Foams

Helical Packing Columns for Preventing Foam Formation: Experimental and Numerical Investigations - Osorio Nesme, Anuhar; Hohagen, Hans; Topic, Nikola; Thünnesen, Julian; Mobarak, Mohammad Mobarak; Lyu, Wenjing; Jahn, Alexander; Kim, Sedong; Delgado, Antonio (Chemical Engineering & Technology, 2022)
Unwanted foaming and liquid bridging inside structured packings have a negative effect on the pressure drop during thermal separation processes. A novel helical design of a packing column for preventing foaming is presented. The effective interfacial area is calculated by numerical simulations. Different designs are analyzed by varying geometrical parameters such as helix pitch, channel opening angle, and number of channels. Different F-factor values and liquid loads are evaluated. Packings with larger helix pitch exhibited lower pressure drop and reduced effective interfacial area. Smaller channel opening angles increased the pressure drop and promoted unstable flow conditions. The novel packings show lower effective interfacial area than existing structured packings, but no foaming was observed in a wide range of operating conditions.
CRIS-Team Scopus Importer:2022-07-22
Keywords: Foaming; Mass transfer; Packing columns; Pressure drop; Structured packing

Modelling and simulation of food foams with different material consistencies - Mobarak, Mohammad Mobarak; Gladbach, Katharina; Chen, Nan; Gatternig, Bernhard; Osorio Nesme, Anuhar; Hussein, Mohamed; Delgado, Antonio (GDL – Symposium Lebensmittelschäume, 2019)

Novel approach for detection of foreign particles in beverages - Forstner, Judith; Benning, Rainer; Procelewska, Joanna; Osorio Nesme, Anuhar; Mauermann, Marc; Hanke, Tilo; Majschak, Jens-Peter; Delgado, Antonio (BrewingScience, 2012)
Foreign particles in food and beverages constitute a serious problem to industry, due to company image and legal responsibility, and the consumer, whose health might be threatened. In this case random testing does not suffice and every container has to be individually tested for absence of such particles. Consequently, there is an urgent need for a reliable, fast and low cost system, which can be automated and which can be applied to filled and closed containers. The presented paper describes a system, which is based on rotatory movement of bottles. Due to their importance glass and PET bottles were used as examples for the approach, forcing particles like glass splinters to move to the wall. Multiple contacts of the particle upon the wall follow from this proceeding and are recorded by a piezo sensor. After processing the resulting signals allow the detection of glass particles with dimensions down to 1 mm x 1 mm x 1 mm in aqueous liquids, like water, beer, butter milk or orange juice. Besides the costs an advantage of the system lies in the characteristic that an optical access is not necessary, both with respect to the material of the bottle and the contained liquid.
UnivIS-Import:2015-04-14:Pub.2012.tech.ITC.stmmec.novela
Keywords: Bverages; Detection system; Food; Foreign particles; Multi contact; Piezo sensor

Numerical simulation of a multi-contact detection technique for foreign particles in closed food containers - Osorio Nesme, Anuhar; schmidt, Tobias R. H.; Beronov, Kamen; Benning, Rainer; Forstner, Judith; Delgado, Antonio (Proceedings in Applied Mathematics and Mechanics, 2009)
UnivIS-Import:2015-04-14:Pub.2009.tech.ITC.stmmec.numeri_94

Particle Tracking Velocimetry zur Bestimmung von Strömungsmustern beim Transport von Proteinschaum in Innengeometrien - Zoheidi, Ladan; Osorio Nesme, Anuhar; Rauh, Cornelia; Delgado, Antonio (Proceedings der 22. GALA-Fachtagung "Lasermethoden in der Strömungsmesstechnik", 2014)
UnivIS-Import:2015-04-17:Pub.2014.tech.ITC.stmmec.partic

Phenomena, mechanisms and structures in wished and unwished foams in matter of biological origin - Gatternig, Bernhard; Osorio Nesme, Anuhar; Almazan Torres, Lidia; Thünnesen, Julian; Beck, Tobias; McHardy, Christopher; Bernstein, Thomas; Luzi, Giovanni; Stahl, Thomas; Rauh, Cornelia; Delgado, Antonio (Proceedings of 2019 World Congress on Advances in Nano, Bio, Robotics, and Energy ANBRE19, 2019)

Prevention or inhibition of foam formation through identification of non-existence domains in the interface in random and structured column-packings - Almazan Torres, Lidia; Osorio Nesme, Anuhar; Delgado, Antonio (Proceedings der 27. GALA-Fachtagung "Experimentelle Strömungsmechanik", 2019)
Undesired foams in reactors occupy the place 11 out of 31 of the causes of column malfunctions. These malfunctions are mainly caused by interfering with transport processes and chemical reactions up to the complete disruption of the process. The wide range of consequences (e.g. waste of time, energy, resources, costs …) affect the production of food as well as of fine chemicals. The influence of the shape of both random and structured packings on foam formation located on trays of the packed columns has not been studied as far as we are concerned. The present work aims for a better understanding of the physics behind the foam formation along with its prevention or inhibition, depending on the packing shape. Possible analytical and numerical solutions for laminar fully-developed flows through random or structured packings under the effect of gravity when the packings are located inside packed columns are investigated. As a starting point, a zigzag geometry with an internal angle 2α is chosen. We propose an analytical expression that describes both the fluid behaviour through the chosen geometry and the shape of the interface generated between the liquid and the gas. Relevant parameters such as surface tension and contact angle are considered in the analysi
Keywords: Foam; packings; column

Rectification, mixing, self-induced oscillations, measurement and control in asymmetrically grooved channels - Beronov, Kamen; Osorio Nesme, Anuhar; Fridmann, I.; Delgado, Antonio (Proceedings in Applied Mathematics and Mechanics, 2008)
UnivIS-Import:2015-03-09:Pub.2008.tech.ITC.stmmec.rectif